Acceptance of home blood glucose monitoring by owners of recently diagnosed diabetic cats and impact on quality of life changes in cat and owner. Issue 8 (August 2018) - Hazuchova, Katarina; Gostelow, Ruth; Scudder, Christopher; Forcada, Yaiza; Church, David B; Niessen, Stijn JM
Objectives: This study aimed to evaluate the acceptance of home blood glucose monitoring (HBGM) by owners of recently diagnosed diabetic cats, and the impact of choosing HBGM on the quality of life (QoL) changes of cat and owner, in addition to glycaemic changes during 6 months of follow-up. Methods: Owners of cats diagnosed with diabetes mellitus (DM) and treated with insulin for 6–20 weeks were divided into an HBGM group and a non-HBGM group, based on their ability and willingness to perform HBGM after a standardised instruction session. The HBGM acceptance level and reasons for acceptance failure were documented; a questionnaire evaluated owners' experiences. For the following 6 months, changes in QoL, measured using the validated DIAQoL-pet quantification tool, and changes in glycaemic control parameters (clinical signs, serum fructosamine, blood glucose curve average/minimal/maximal/pre-insulin blood glucose) were compared between HBGM and non-HBGM groups at months 1, 3 and 6, as well as within the groups between baseline and months 1, 3 and 6. Results: Thirty-eight cats were enrolled; 28 (74%) entered the HBGM group. There was no significant difference between groups in overall DIAQoL-pet score or glycaemic control parameters at any time point apart from the maximal blood glucose at month 6 (lower in the HBGM group). However, the DIAQoL-pet score, including indicators of owner worry about DM, worry about hypoglycaemia and costs, as well as glycaemic parameters, improved at all time points within the HBGM group but not within the non-HBGM group. Remission occurred in 9/28 (32%) HBGM group cats and 1/10 (10%) non-HBGM group cats ( P = 0.236). Conclusions and relevance: HBGM was adopted successfully by most diabetic cat owners. Despite the extra task, positive changes in QoL parameters occurred in the HBGM group and not in the non-HBGM group. Although no difference was found in glycaemic control between the HBGM and non-HBGM groups during the 6 months of follow-up, significant glycaemic improvements were documented in the HBGM group.